A study on different fault characteristics using wavelet and fast Fourier transforms - E., Engu; K., Ramar; R., Montano; V., Cooray (2008)
An investigation on different types of faults namely: open-circuit (OC), short-circuit (SC), high impedance fault (HIF) and the fault caused by direct lightning strike (LS) on the transmission line has been done using Alternative Transient Program/Electromagnetic Transient Program (ATP/EMTP) and MATLAB Toolbox. The characteristic of the faults in terms of their corresponding frequency spectrum, the polarity of incident- and reflected-wave from fault point, and the neighboring and/or remote end busbar signals has been studied and verified for the possibility to differentiate the type of fault occurred. For this purpose, the fault point on the wave has been created at the moment when the voltage signal reaches its peak and also when it is close to zero. Both, Wavelet Transform (WT) and Fast Fourier Transform (FFT) methods have been implemented in the study to extract and analyze the information associated with transient signal generated by the fault simulated at both, sending and receiving end busbars. Model of the network used in this study is taken from [1].